Symmetry Decrease between Self‐Assembled Circular TiO4N2‐Based Helicates. Issue 36 (12th August 2020) - Khalil, Georges; Barloy, Laurent; Kyritsakas, Nathalie; Kauffmann, Brice; Chaumont, Alain; Henry, Marc; Mobian, Pierre
Abstract : A multicomponent self‐assembly reaction involving a bis‐biphenolato ligand (LH4 ), a 2, 2'‐bipyrimidine chelate substituted by two (anthryl)vinyl moieties (bAnt) and Ti(O i Pr)4 was investigated. An assembly [Ti3 (L)3 (bAnt)3 ], composed of three homochiral TiO4 N2 nodes, was characterized as being the thermodynamically‐end product. The crystal structure of this circular helicate highlighted an absence of symmetry for this compact compound. DOSY 1 H NMR indicated that the nuclearity observed in the solid state for [Ti3 (L)3 (bAnt)3 ] was maintained in solution. An intermediate formulated as [Ti4 (L)4 (bAnt)4 ] was isolated. The structural analysis revealed that [Ti4 (L)4 (bAnt)4 ] was a symmetrical circular hollow helicate composed of four homochiral metallovertices. This study, supported by DFT calculation, brought some evidences on the sequences and the reasons leading to the symmetry decrease for this self‐assembly process. Abstract : A symmetry decrease is observed in the course of a self‐assembled process generating circular architectures constructed around TiO4 N2 nodes. The origins of this phenomenon are investigated.